(untitled) (Global Journal of Management and Business Research, 2022)
The primary aim of the study was to examine the impact of innovative leadership practices on strategic intelligence in telecommunication companies in Jordan. Data were primarily gathered through the questionnaires distributed to a random sample of (125) managers. In total, (116) responses were received, including (4) invalid to statistical analysis due to uncompleted or inaccurate. Hence, the final sample contained (112) answers suitable to analysis requirements. Structural equation modeling (SEM) was conducted to test hypotheses. The results showed that all innovative leadership dimensions have a positive impact relationship on strategic intelligence except changeability which has no impact on Strategic Intelligence. According to the results reached by the analysis, the researchers present several recommendations to decision-makers to adopt to enhance the desired results through strategic intelligence in adopting crisis management strategies in the telecommunication companies in Jordan.